ナンキョク ショウワ キチ シュウヘン カラ サイシュウ サレタ Bryum ゾク ノ バイスウ セイ - 神田, 啓史; カンダ, ヒロシ; 岡田, 博; オカダ, ヒロシ; Kanda, Hiroshi; Okada, Hiroshi (1990)
P(論文) 昭和基地周辺から採集された蘚類2種, Bryum pseudotriquetrum (HEDW.) GAERTN., MEYER et SCHERB.およびB. amblyodon C. MUELL.の染色体数について分析した。観察されたほとんどの標本は2種ともn=20を示した。しかしながら, B. pseudotriquetrumと同定された一試料にn=30が見いだされた。これは基本数n=10の3倍体と考えられる。この3倍体の配偶体の形態は2倍体との間に著しい差は見られなかったが, 葉はより柔らかくしわがより, 葉の細胞はより長く, 葉の先端部は長くとがり, 葉の中肋も長く突出することがある等の特長が認められた。本種の3倍体はこれまでソ連で報告されたことがあるが, 倍数性の発生率は両極域など高緯度地方に行くにしたがって増加することが予測される。 Bryum pseudotriquetrum (HEDW.) GAERTN., MEYER et SCHERB. and B. amblyodon C. MUELL. collected from the Syowa Station area, Antarctica are karyologically studied with particular regard to the polyploidy. Almost all samples of these two species showed to have n=20. This may be the diploid level derived from x=10. In the present study, however, the triploid level (n=30) was confirmed in one sample of B. pseudotriquetrum, and the morphological features of chromosomes, leaves and cells are compared with those of n=20. Such polyploidy was hitherto unknown in this species. It is possible to say that the polyploidy increases in incidence with latitude in the polar areas. departmental bulletin paper